2020
DOI: 10.3892/ijmm.2020.4599
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑17 contributes to the suppression of the inflammatory response in lipopolysaccharide‑induced acute lung injury in mice via targeting the toll‑like receptor 4/nuclear factor‑κB pathway

Abstract: Acute lung injury (ALI) is a common lung disease with a high mortality rate, which is characterized by an excessive uncontrolled inflammatory response. MicroRNA (miR)-17 has previously emerged as a novel regulatory molecule of inflammatory response in various complex diseases; however, the anti-inflammatory action and associated molecular mechanisms of miR-17 in ALI have not been fully elucidated. The aim of the present study was to investigate the role of miR-17 in the inflammatory response in ALI and to eluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Interestingly, recent studies have shown that some miRNAs that are potentially expressed in sEVs can alleviate ALI. For instance, miR-490, an miRNA that exists in the sEVs of mast cells [ 11 ], has been reported to alleviate sepsis-induced ALI in newborn mice, whereas miR-17, which can be found in human umbilical cord MSC-derived sEVs [ 12 ], had been shown to suppress inflammatory responses in lipopolysaccharide (LPS)-induced ALI [ 13 ]. Moreover, miR-21-5p, another microRNA highly expressed in MSC-derived sEVs [ 14 ], had been reported to alleviate hyperoxic ALI in rats [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, recent studies have shown that some miRNAs that are potentially expressed in sEVs can alleviate ALI. For instance, miR-490, an miRNA that exists in the sEVs of mast cells [ 11 ], has been reported to alleviate sepsis-induced ALI in newborn mice, whereas miR-17, which can be found in human umbilical cord MSC-derived sEVs [ 12 ], had been shown to suppress inflammatory responses in lipopolysaccharide (LPS)-induced ALI [ 13 ]. Moreover, miR-21-5p, another microRNA highly expressed in MSC-derived sEVs [ 14 ], had been reported to alleviate hyperoxic ALI in rats [ 15 ].…”
Section: Introductionmentioning
confidence: 99%